Konsep Supervisi dalam Perspektif Al-Quran - Hafidh Izzuddin; Syarif Hidayat (STAI Terpadu Yogyakarta, 2023)
The quality of education in Indonesia is at the middle level of all countries in the world. Therefore, improving the quality of education is something that needs to be done. One way to improve the quality of education is to carry out supervision. With supervision, will improve the quality of teachers so that student achievement will also increase. This study uses the literature study method, by examining sources that are relevant to the scope of educational supervision. Be it from books, journals, articles or other sources. The approach used is descriptive-qualitative. By describing each qualitative data found descriptively. Supervision is a form of supervisory action carried out by the principal in order to develop professionalism, increase motivation and monitor the quality of teachers in acting in the classroom. So that the goals of educational institutions can be achieved. With the development of teachers, students are expected to be able to maximize their potential and increase achievement. Implementation of permanent supervision based on existing steps and principles so as to maximize results. Therefore, supervision is needed in educational institutions, in order to improve the quality and professionalism of teachers which can have an impact on increasing student achievement so that the quality of education in Indonesia also increases. Keywords: Supervision, Education, Al Quran